A dinâmica da cana-de-açúcar no Brasil: 2002 a 2012 - Lima, Débora Juliene Pereira (2016)
This thesis analyses the dynamics of sugarcane in Brazil, highlighting its impact on employment from 2002 to 2012. Data from the Municipal Agricultural Research (PAM) of the Brazilian Institute of Geography and Statistics (IBGE) revealed that sugarcane is the crop that has expanded the most in terms of footprint, and this expansion has taken place toward the Midwest region. The production of sugarcane is concentrated in the states of São Paulo and Minas Gerais, but other states, such as Goiás and Mato Grosso do Sul, increased their share in the national production. The impact that this new dynamic sparked on employment was evaluated based on microdata from the National Survey by Household Sampling (PNAD) using Stata software. This data revealed that in a period of increasing trend in national employment, there was a reduction in the number of workers in sugarcane and other crops that have been selected for comparison: coffee, corn, soybean and rice. Clear upward trend was found in the proportion of employed people with a formal contract in sugarcane, although the proportion of informal workers have not changed. Among the selected crops, sugarcane has the highest proportion of formal workers, while in the others, much of the labour force is made up of self-employed workers. Furthermore, it was noticed that, although there was an increase in the proportion of machine operators in sugarcane, most of the labour force of this crop are cane cutters, even in the central-west region of the country. To measure the behaviour of the quality of employment in these fields, the Employment Quality Index (EQI) was calculated with different weights of its partial indicators. The construction of this index was based on some PNAD microdata, such as proportion of formal workers, proportion of workers above 15 years of age, the proportion of workers with a work week of up to 44 hours, the proportion of workers who contributed to social security, among others. The results of these indicators, in particular, deserve to be highlighted: the crops of sugarcane and soybean have the highest proportion of overworked workers. These crops are precisely those with the highest degree of mechanization. Moreover, IQEs showed an upward trend in all selected crops and a higher value for sugarcane and soybean. This result is due to the greater degree of work formalization and higher yields of these crops.